2017
DOI: 10.1111/nhs.12368
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of discharge documentation after hospitalization for stroke patients discharged home in Australia: A cross‐sectional, pilot study

Abstract: In this cross-sectional study, we evaluated the quality of discharge documentation for stroke patients discharged home. Participants were stroke patients discharged from a regional tertiary acute and rehabilitation hospital in Australia from 2014 to 2015. Compliance with expected discharge documentation and its relationship with readmission was measured using an audit instrument for stroke patients (n = 54), and a post-discharge survey of carers was conducted. There were deficits in the documentation of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…In addition, referrals to the community stroke program were reported to be low, and there is a 3 month waiting time for these programs. Previous studies have emphasized the risk of suffering high carer stress (Aziz et al, 2016;Ekstam, Johansson, Guidetti, Eriksson, & Ytterberg, 2015;Kable et al, 2018;King et al, 2010). They also highlight the significance and complexity of the carer role during transitions between services and in maintaining continuity of care (Ghazzawi et al, 2016;Hvalvik & Reierson, 2015), and associated difficulty for carers when stroke survivors are discharged home.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, referrals to the community stroke program were reported to be low, and there is a 3 month waiting time for these programs. Previous studies have emphasized the risk of suffering high carer stress (Aziz et al, 2016;Ekstam, Johansson, Guidetti, Eriksson, & Ytterberg, 2015;Kable et al, 2018;King et al, 2010). They also highlight the significance and complexity of the carer role during transitions between services and in maintaining continuity of care (Ghazzawi et al, 2016;Hvalvik & Reierson, 2015), and associated difficulty for carers when stroke survivors are discharged home.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the global advancement in stroke treatment and care, recent literature has reported that 40–60% of stroke survivors experience moderate‐to‐severe disabilities that require rehabilitative or long term care (Van Mierlo, van Heugten, Post, Hoekstra, & Visser‐Meily, ). As a result, stroke survivors rely heavily on their families for ongoing care, recovery, and even palliative care over long periods (Costa, Costa, Martins, Fernandes, & Brito, ; Hayashi, Hai, & Tai, ; Kable, Pond, Baker, Turner, & Levi, ). These caregiving roles could increase stress on caregivers, thus having a negative consequence on their health status (Em et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Despite the recent policy focus on maintain and enhance continuity of care (COC) within hospital care, [3] rehabilitation research reports that there is limited communication, transfers delays and administrative barriers between rehabilitation team and other services. [1,4,5] Inpatients receiving physiotherapy report a lack of transfer of information and consistency of care between professionals. These concerns are related to content, synchronization, or sequence of the physiotherapy activities.…”
Section: Introductionmentioning
confidence: 99%
“…These measures have examined features of the chronology of sequential care or transfers delays. [2,4,5,7,8,13,14] Likely, continuity from patient's perspective is not often evaluated because of the lack of an agreed definition and suitable measurement tools.…”
Section: Introductionmentioning
confidence: 99%